Analyzing the content of the poetic discourse in the poem (Bant Souad) – A study in light of the solidarity strategy – - Al-Btoosh, Hosam Mohammad (Arab Journal for Sciences and Research Publishing, 2021)
The study monitors the solidarity strategy in the poem Al-Barda by Kaab Bin Zuhair, which is an apology directed to the Prophet, and thrown in his hands, and considered one of the eyes of Arab poetry in praise, by revealing the mechanisms that Kaab Bin Zuhair employed in his poem, in which he took into account the position of the Holy Prophet, and his position The same after he had wasted blood.The conversational solidarity strategy expresses the nature of the relationship between the producer and the recipient, which is a relationship of affection and gain for the recipient's satisfaction and the consolidation of the relationship with him, so the research was based on clarifying the pillars of requesting friendliness and forgiveness, and the beginning of a new life for the poet started by apologizing to the Prophet.The words of politeness, kindness, apology and recognition of the Prophet’s standing in his heart appeared, and that he was in solidarity with the call that was carried by the Muslims.
Keywords: Solidarity strategy; Pragmatics; Ka'b ibn Zuhayr; Banat Su'ad